Cytochrome P450 Monooxygenase and Pyrethroid Resistance in Anopheles: A Narrative Review - I Gusti Ayu Avinya Chintya Devi; Dewa Ayu Agus Sri Laksemi; Putu Ayu Asri Damayanti (GLOBAL HEALTH SCIENCE GROUP, 2026)
Malaria remains a major global public health problem, with approximately 282 million cases reported in 2024. Although vector control interventions such as long-lasting insecticide-treated nets (LLINs) and indoor residual spraying (IRS) have significantly reduced malaria transmission, their effectiveness is increasingly compromised by pyrethroid resistance in Anopheles mosquitoes. This review examines the role of cytochrome P450 monooxygenase enzymes in mediating pyrethroid resistance. A literature search was conducted in PubMed, Springer, and Google Scholar for articles published between 2016 and 2026 using the keywords “Cytochrome P450,” “P450 monooxygenase,” “Insecticide Resistance,” “metabolic resistance,” “Pyrethroid,” “Anopheles,” and “malaria vector.” Of 10,854 articles identified, 142 were screened, and six relevant studies were included, focusing on resistance mechanisms, P450 characteristics, gene regulation, and vector control implications. The findings indicate that overexpression of specific P450 genes significantly enhances the detoxification of pyrethroids, thereby reducing insecticide susceptibility. Furthermore, interactions between metabolic resistance and target-site mutations contribute to elevated resistance levels. Recent evidence suggests that non-coding RNAs (ncRNAs) regulate detoxification pathways and contribute to adaptive resistance. In conclusion, insecticide resistance in Anopheles is a multifactorial process involving genetic, biochemical, and regulatory mechanisms. Understanding these mechanisms is crucial for developing more effective and sustainable vector control strategies.